Quality of Life for 19,114 participants in the ASPREE (ASPirin in Reducing Events in the Elderly) study and their association with sociodemographic and modifiable lifestyle risk factors - Stocks, N.; González-Chica, D.; Woods, R.; Lockery, J.; Wolfe, R.; Murray, A.; Kirpach, B.; Shah, R.; Nelson, M.; Reid, Christopher; Ernst, M.; McNeil, J. (Springer, 2018)
Purpose: To explore the relationship between sociodemographic and lifestyle variables with health-related quality of life (HRQoL) of a large cohort of ‘healthy’ older individuals. Methods: The sample included individuals aged 65+ years from Australia (N = 16,703) and the USA (N = 2411) enrolled in the ASPirin in Reducing Events in the Elderly (ASPREE) multicentre placebo-controlled trial study and free of cardiovascular disease, dementia, serious physical disabilities or ‘fatal’ illnesses. The associations with the physical (PCS) and mental component scores (MCS) of HRQoL (SF-12 questionnaire) were explored using multiple linear regression models from data collected at baseline (2010–2014). Results: The adjusted PCS mean was slightly higher in the USA (49.5 ± 9.1) than Australia (48.2 ± 11.6; p < 0.001), but MCS was similar in both samples (55.7 ± 7.5 and 55.7 ± 9.6, respectively; p = 0.603). Males, younger participants, better educated, more active individuals, or those currently drinking 1–2 alcoholic drinks/day showed a better HRQoL (results more evident for PCS than MCS), while current heavy smokers had the lowest physical HRQoL in both countries. Neither age, walking time, nor alcohol intake was associated with MCS in either cohort. Conclusions: Baseline HRQoL of ASPREE participants was higher than that reported in population-based studies of older individuals, but the associations between sociodemographic and lifestyle variables were consistent with the published literature. As the cohort ages and develops chronic diseases, ASPREE will be able to document HRQoL changes.